Laser-induced microinjury of the corneal basal epithelium and imaging of resident macrophage responses in a live, whole-eye preparation - Gulka, Sebastian M. D.; Gowen, Brent; Litke, Anastasia M.; Delaney, Kerry R.; Chow, Robert L. (Frontiers in Immunology, 2023)
The corneal epithelium is continuously subjected to external stimuli that results in varying degrees of cellular damage. The use of live-cell imaging approaches has facilitated understanding of the cellular and molecular mechanisms underlying the corneal epithelial wound healing process. Here, we describe a live, ex vivo, whole-eye approach using laser scanning confocal microscopy to simultaneously induce and visualize short-term cellular responses following microdamage to the corneal epithelium. Live-cell imaging of corneal cell layers was enabled using the lipophilic fluorescent dyes, SGC5 or FM4-64, which, when injected into the anterior chamber of enucleated eyes, readily penetrated and labelled cell membranes. Necrotic microdamage to a defined region (30 μm x 30 μm) through the central plane of the corneal basal epithelium was induced by continuously scanning for at least one minute using high laser power and was dependent on the presence of lipophilic fluorescent dye. This whole-mount live-cell imaging and microdamage approach was used to examine the behavior of Cx3cr1:GFP-expressing resident corneal stromal macrophages (RCSMs). In undamaged corneas, RCSMs remained stationary, but exhibited a constant extension and retraction of short (~5 μm) semicircular, pseudopodia-like processes reminiscent of what has previously been reported in corneal dendritic cells. Within minutes of microdamage, nearby anterior RCSMs became highly polarized and extended projections towards the damaged region. The extension of the processes plateaued after about 30 minutes and remained stable over the course of 2-3 hours of imaging. Retrospective immunolabeling showed that these responding RCSMs were MHC class II+. This study adds to existing knowledge of immune cell behavior in response to corneal damage and introduces a simple corneal epithelial microdamage and wound healing paradigm.